Majlis Perbandaran Selayang android application MPS e-aduan mobile / Mohammad Azree Yahaya - Yahaya, Mohammad Azree (2014)
Selayang Municipal Council (MPS) is a local authority that involve in serving multiple services and authorization towards local resident within Selayang district. Due to increasing of information and to serve ease communication and customer satisfaction, MPS plan to have an android application to enables local resident to lodge report as well suggestion to MPS improvement. The planned android system also should be able to interact actively within the users and easy to manage. For this project, the suitable project development methodology to be implemented is Rapid Application Development (RAD). Seeing as this project need to be deliver within ten (10) weeks or less than three (3) months, therefore, implementing RAD as project development methodology are relevant for diminutive timeline project. In view of the fact that this project will implement RAD as development methodology, it seems its cover all aspect related to the development and installation of the information system from the process of gathering information until implementation. This project also being approves to success and meets the requirement required by upper management. Therefore, the record on the database for this android system will not be exposing to unauthorized people due to the privacy and security issue. For this project, the attached softcopy system is the exact system that being used in the unit but with filtered data. As conclusion, this project was successfully delivered within the expected time with superb reorganization from the user and customer.